Nayantara Sahgal : a study of her fiction and non-fiction, 1954-1974 - Krishna Rao, A. V. (Angara Venkata), 1937-1995 (M. Seshachalam, 1976)
On the writings of the Indo-Anglian authoress Nayantara Pandit Sahagal, b. 1927.